Direct Numerical Simulation of Particle-laden Flow Around an Obstacle at Different Reynolds Numbers. Issue 1 (April 2021) - Lin, Shengxiang; Xia, Huanxiong; Zhang, Zhenyu; Liu, Jianhua; Wang, Honglei
Abstract: Inspired by the practical operation of the fluid machineries, direct numerical simulation of fluid with a lot of finite-size particles flowing around a large-size obstacle at three different Reynolds numbers is implemented by using a two-way coupled finite-volume, discrete-element and immersed-boundary method. The results show that, for a low Reynolds number Re =20, the flow is dominated by viscosity, and under the circumstances of a small Stokes number, the particles follow fluid streamlines closely. The flow suggests regular movement characteristics of laminar flow, although the vortices behind the obstacle tend to collapse under the perturbation of particles. For a moderate Reynolds number Re =100, the phenomenon of vortex shedding is also observed. Due to the centrifugal force induced by the vortices, particles are distributed around the main vortices behind the obstacle, forming particle-free zones in these vortices. For a high Reynolds number Re =300, the flow is chaotic. The vortices of many sizes appear irregularly in the domain and the distribution of particles tends to be uniform.